PENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL NUMBERED HEAD TOGETHER (NHT) DI KELAS IV SD NEGERI 17 SUNGAI LIMAU - BELINA, LAILA (Universitas Negeri Padang, 2014)
Abstract This research was intended to describe the improvement of the students’ learning achievement in Social Science by using NHT model in grade IV of SDN 17 Sungai Limau. This was a Classroom Action Research which applied both qualitative and quantitative approaches. The subject of the research was 20 student in grade IV. The result of the research revealed that from cycle I to cycle II, the quality ofthe Lesson Plan Increaased from 69,64% to 85,71%, the teacher’s aspect increased from 79,1% to 88,88%, and the student’s aspect increased from 77,7% to 91,6%. Thus, the use of Numbered Head Together (NHT) approach could increase the students’ learning Achievement in grade IV of SDN 17Sungai Limau. Key Term : Learning Achievement, NHT Model